Protestants and the cult of the saints in German-speaking Europe, 1517-1531 - Heming, Carol Piper, 1945- (Sixteenth century essays & studies, 2003)
"Through the analysis of 180 pamphlets published between 1500 and 1530 by reformers in German-speaking Europe, Carol Heming shows the struggle Protestants faced in purging the cult of the saints from their culture and religion. Heming examines why Reformation leaders so strongly and universally denounced the cult of the saints and whether the holy patrons disappeared from Protestant areas without benefit of champion or defender."--Jacket